TINGKAT STRES KERJA DAN STRATEGI KOPING GURU SD DALAM IMPLEMENTASI KURIKULUM 2013 - Nadia Yuli Pertiwi; Ice Yulia Wardani (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2019)
Teachers quality is greatly influence education at the whole level of education including elementary school level. Teachers are one of the jobs with high levels of work stress. One of the causes of work stress is educational curriculum. This study aims to determine the level of stress and coping strategy of elementary school teachers in implementation of curriculum 2013 in Bogor Central District, Bogor. The design in this research used descriptive quantitative with cross sectional approach. This study involved 222 elementary schools teachers in Bogor Central District selected by purposive sampling. The results of this study illustrate the majority of elementary schools teachers in Bogor Central District (81,5%) experience moderate stress. Each dimension of work stress, occupational role (ORQ), personal strain (PSQ) and personal resources (PRQ) show that the majority of teachers experience moderate stress. The type of coping strategy that is most often used by elementary schools teachers in Bogor Central Districtis is problem focused coping (54,6%). The results of this study recommend nurses to be able for collaboration with school to facilitate activities that could reduce stress and use appropriate coping strategies.Keywords: Elementary School Teacher, work stress, curriculum 2013, coping strategy